Analysis of Factors Related to the Occurance of Fall in Elderly - Puji Suwariyah; Intan Diah Pramithasari (GLOBAL HEALTH SCIENCE GROUP, 2019)
Elderly is very susceptibleto fall in, this is because their all organ systems have decreased. The occurance of falls in the elderly is influenced by several factors such as age, environment, cardiovascular disorders, and physical activity. The writer wanted to analyze factors related to the risk of falling occurance in the elderly in the District Health Center of Maos, Cilacap Regency. This type of research is a correlational study with a cross sectional approach. The number of samples of this study were 52 elderly taken using consecutive sampling. The analysis used chi square test. The risk of falling occurance rates for the elderly in the Maos Community Health Center in Cilacap Regency was mostly in the no-risk category of 36 respondents (69.2%). Chi square test results showed that there were age factors (p 0.033), environment (p 0,000), cardiovascular disorders (p 0.011), and physical activity (p 0,000) with the risk of falling in the elderly in the Maos Puskesmas Area, Cilacap Regency. There is a relation between age, environment, cardiovascular disorders and physical activity with the risk of falling in the elderly in the Maos Puskesmas in Cilacap Regency. Keywords: physical activity, cardiovascular disorders, falling risk